Evaluation of Drug Related Problems of Antihypertensive Drugs in Inpatient Hypertensive Patients at the Latemmamala Regional General Hospital, Soppeng Regency for the January-March 2023 Period - Yuliana, Dewi; Salam, Rika Amalia; Arifin, Sukmawati (Journal of Pharmaceuticals and Natural Sciences, 2024)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements taken five minutes apart at rest. Problems caused by drug abuse are called DRPs (Drug Related Problems). The occurrence of DRPs is known to have a detrimental effect on patient quality of life, increased mortality and high medical costs. This study aims to determine the incidence of DRPs and the types of DRPs that occur in hypertensive patients at Latemmamala Hospital, Soppeng Regency. This study is a type of non-experimental descriptive research conducted retrospectively using secondary data in medical records where samples were selected using purposive sampling technique. The results showed that of the 78 samples consisting of 42 women (53.85%) and 36 men (46.15%), all of which met the inclusion and exclusion criteria, showed that the age prevalence was more prone to hypertension at the age of 56-75 years as many as 47 patients (60.26%). There were 46 cases out of 43 patients who had the potential to experience DRPs. The most DRPs that occurred were in the case of C1.4 as many as 26 cases (56.52%), then C1.1 as many as 20 cases (43.48%).